"I, Impostor"- Mike Nelson-British Pavilion : 54th International Art Exhibition- La Biennale di Venezia 2011 - Nelson, Mike; Cameron, Dan; Williams, Emma; Latty, Gemma; Withers, Rachel; Riley, Richard (London; British Council, 2011)
Conceived and created for the British Pavilion at the 54th International Art Exhibition - la Biennale di Venezia 2011
English
Keywords: N4390-5098 Visual Arts- Exhibitions; Pavilion catalog; UK